2023
DOI: 10.1039/d3sc01086d
|View full text |Cite
|
Sign up to set email alerts
|

In vivo biodistribution of kinetically stable Pt2L4 nanospheres that show anti-cancer activity

Eduard O. Bobylev,
Renzo A. Knol,
Simon Mathew
et al.

Abstract: There is an increasing interest in the application of coordination-based spherical assemblies (CBSAs) in a bio medicinal context, as they can offer non-classical distribution in organisms compared to molecular substrates...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…In the future, one promising alternative for developing more stable metallacages is the use of more kinetically inert metal–ligand bonds, e.g., by using Pt­(II) as a substitute for Pd­(II). This approach has been demonstrated to yield systems with enhanced stability . Overall, our results show that, although challenging, the synthesis of SCC-based radiopharmaceuticals is possible and, upon optimization, can render systems with increased functionality that can be foreseen as a new generation of theranostic agents.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In the future, one promising alternative for developing more stable metallacages is the use of more kinetically inert metal–ligand bonds, e.g., by using Pt­(II) as a substitute for Pd­(II). This approach has been demonstrated to yield systems with enhanced stability . Overall, our results show that, although challenging, the synthesis of SCC-based radiopharmaceuticals is possible and, upon optimization, can render systems with increased functionality that can be foreseen as a new generation of theranostic agents.…”
Section: Discussionmentioning
confidence: 80%
“…Relatively few examples exist where SCCs have been employed as molecular imaging agents, despite the plethora of strategies for achieving light-emitting scaffolds . For example, SCCs can include ligands, metal centers, or pendant functional groups that confer luminescent properties on the SCCs in order to study their cellular accumulation, subcellular distribution, and overall fate in biological systems by optical imaging methods. In this context, two-dimensional (2D) SCCs as boron dipyrromethene (BODIPY)-based, highly emissive Pt­(II) supramolecular triangles ( Pt-BODIPY , Figure a) have been reported, which were endowed with combined phototherapy–chemotherapy effects. Moreover, the near-infrared (NIR)-II emissive Ru­(II) metallacycle ( Ru1085 , Figure b), which shows precise fluorescence imaging-guided and long-term monitored chemophototherapy against A549 lung tumors, is highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…To track the distribution of the nanoplatforms, Cy5-labeled BP-PGA 50 and PGA 50 NPs were administered via intranasal instillation in the mouse model, and the biodistribution was monitored at 0, 1, and 7 d postadministration. 44 The fluorescence signals in the nose and lungs decreased quickly at 1 day after instillation, particularly for PGA 50 NP-treated mice (Figure 5A). Then, the mice were sacrificed, and the MBs, lungs, and other major organs were isolated.…”
Section: Resultsmentioning
confidence: 98%
“…Collectively, our findings demonstrated that BP-PGA 50 nanosheets with their 2D nanostructure effectively inhibited both TLR9 stimulation and NET formation via cfDNA scavenging. 44 The fluorescence signals in the nose and lungs decreased quickly at 1 day after instillation, particularly for PGA 50 NP-treated mice (Figure 5A). Then, the mice were sacrificed, and the MBs, lungs, and other major organs were isolated.…”
Section: Analysis Of Cfdna and Net Levels In Nasalmentioning
confidence: 98%
“…Therefore, to enhance these types of applications there is a need to develop more kinetically robust MSAs. [195][196][197][198] The majority of heterometallic MSAs developed to date feature both inert and liable metal ions. Thus, it would be expected that those systems would be more robust than the related homometallic systems.…”
Section: Discussionmentioning
confidence: 99%